2022
DOI: 10.1017/eso.2022.43
|View full text |Cite
|
Sign up to set email alerts
|

The Peruvian Amazon Company: An Accounting Perspective

Abstract: This article presents an analysis of the operations of the Peruvian Amazon Company through an accounting lens. It is suggested that a focus on asset categories augments our knowledge of the company’s exploitation of the land and Indigenous peoples of Amazonia. In particular, the study explores the PAC’s questionable ownership of estates in the Putumayo, what its approach to valuing those estates implied about enslavement, how its treatment of “expenses of conquest” and the inclusion of armaments on the balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…The capacity of shadow, alternative or counter accounts to give voice to oppressed groups and create visibilities that disrupt power relations is also an established theme in the critical accounting literature (Thomson et al, 2015;Vinnari and Laine, 2017). It has been suggested that counter accounts are a means of 'talking back' and thus have emancipatory potential (Dey et al, 2011;Gallhofer et al, 2006;Spence, 2009;Walker, 2022). Although alternative accounts are usually generated by informed external observers, they may also be composed by the oppressed themselves.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…The capacity of shadow, alternative or counter accounts to give voice to oppressed groups and create visibilities that disrupt power relations is also an established theme in the critical accounting literature (Thomson et al, 2015;Vinnari and Laine, 2017). It has been suggested that counter accounts are a means of 'talking back' and thus have emancipatory potential (Dey et al, 2011;Gallhofer et al, 2006;Spence, 2009;Walker, 2022). Although alternative accounts are usually generated by informed external observers, they may also be composed by the oppressed themselves.…”
Section: Concluding Discussionmentioning
confidence: 99%